Radiographic evaluation of the painful adolescent and young adult hip - Rishi Sinha, BA; William Z. Morris, MD; Henry B. Ellis, MD; James McGinley, BS; David A. Podeszwa, MD; Daniel J. Sucato, MD; Jeffrey J. Nepple, MD; John C. Clohisy, MD (Elsevier, 2024)
ABSTRACT: Radiographic evaluation of hip pain in adolescents and young adults is an important component of the assessment to aid in the identification of the cause of pain, distinguish between etiologies of early hip degeneration such as acetabular dysplasia (instability) and femoroacetabular impingement, and guide further workup and management. Recent advances in radiographic assessment include the importance of obtaining a standing anterior-posterior radiograph to illustrate the functional position of the pelvis, the use of anterior and posterior wall indices to illustrate anterior and posterior wall coverage and the importance of interpreting radiographic measures in the context of a patient's sagittal balance. Advances in magnetic resonance imaging, computed tomography, and ultrasound have also occurred and can provide further diagnostic clarity. The purpose of this work is to review the literature to provide a systematic approach to the radiographic evaluation of hip pain in skeletally mature adolescents and young adults. Key Concepts: (1) The standing AP pelvis, 45° Dunn, and false-profile views provide a preliminary comprehensive radiographic assessment of the symptomatic hip in the skeletally mature adolescent and young adult and help to distinguish between instability and impingement. (2) The Lateral Center Edge Angle (LCEA) should be augmented by the anterior center edge angle (ACEA), anterior wall index (AWI), and posterior wall index (PWI) to obtain a more complete understanding of 3-dimensional femoral head coverage from plain radiographs. (3) While the crossover and posterior wall signs on radiographs can be helpful in screening for acetabular retroversion and anteversion, CT should be used to confirm if considering reorientation or resection. (4) Cam morphology should be quantitatively assessed using the alpha angle and head-neck offset on the 45° Dunn view. (5) Dynamic ultrasound may be useful in illustrating the motion associated with impingement and instability in real-time but may be limited by the technician-dependent nature of this modality.